2013
DOI: 10.1088/0031-9155/58/9/2879
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of secondary particles in proton and carbon-ion therapy: a comparison between GATE/Geant4 and FLUKA Monte Carlo codes

Abstract: Monte Carlo simulations play a crucial role for in-vivo treatment monitoring based on PET and prompt gamma imaging in proton and carbon-ion therapies. The accuracy of the nuclear fragmentation models implemented in these codes might affect the quality of the treatment verification. In this paper, we investigate the nuclear models implemented in GATE/Geant4 and FLUKA by comparing the angular and energy distributions of secondary particles exiting a homogeneous target of PMMA. Comparison results were restricted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 55 publications
2
90
0
Order By: Relevance
“…Plastic-to-water conversion factor measured experimentally (refer to equation (3)) and derived from Monte Carlo simulations (refer to equation (5) the BIC model (Folger et al 2004) in Geant4. Böhlen et al (2010) and Robert et al (2013) compared FLUKA and Geant4 nuclear models for carbon-ion beams and for proton and carbon-ion beams, respectively, and both studies reported substantial deviations between codes. Moreover, ICRU Report 63 (2000) estimated uncertainties of the order of 5%-10% on the total nonelastic cross sections and 20%-30% on the angle-integrated production cross sections for secondary particles in proton beams.…”
Section: Plastic #1mentioning
confidence: 99%
“…Plastic-to-water conversion factor measured experimentally (refer to equation (3)) and derived from Monte Carlo simulations (refer to equation (5) the BIC model (Folger et al 2004) in Geant4. Böhlen et al (2010) and Robert et al (2013) compared FLUKA and Geant4 nuclear models for carbon-ion beams and for proton and carbon-ion beams, respectively, and both studies reported substantial deviations between codes. Moreover, ICRU Report 63 (2000) estimated uncertainties of the order of 5%-10% on the total nonelastic cross sections and 20%-30% on the angle-integrated production cross sections for secondary particles in proton beams.…”
Section: Plastic #1mentioning
confidence: 99%
“…The relevance of existing discrepancies in numerical models (see for example ref. [6,7]) should be discussed in the context of clinical applications. The detailed quantitative evaluation of biological dose distributions would require the simulation of a carbon ion treatment field including radiobiological modeling.…”
Section: Nuclear Physics: What Really Mattersmentioning
confidence: 99%
“…This is managed in treatment by prescribing a margin around the target volume as is commonly done in radiotherapy for other reasons, and by trying to ensure that the optimised treatment plan is robust against density uncertainties [145]. Because of this limitation a number of techniques -some to be used in combination with each other -are being studied to improve the prediction of proton stopping, and include techniques such as magnet resonance imaging (MRI), and monitoring of secondary particles produced during treatment [146][147][148].…”
Section: Imaging With Acceleratorsmentioning
confidence: 99%